Memprediksi Jumlah Produksi Roti Dengan Menerapkan Metode Monte Carlo - Nur Rohmah, Fitri; Arwin Dermawan, Dodik; Andriani, Anita (Inovate, 2021)
The process of predicting the amount of production is useful for reducing the level of producer losses due to inaccuracy in determining the amount of production, so that the stock of goods which usually experience accumulation or even out of stock is expected no longer. The purpose of this research itself is to design a system using Monte Carlo as a method to predict the amount of bread production. In the Monte Carlo method there is one step in the process using random numbers. The method used to generate random numbers this time is using the Linear Congruent Method (LCM). Hasil method. The results of this research is an application to facilitate the admin of the production sector to predict the amount of bread production for the next day. The prediction of the amount of production for this type of comb bread yields 1461 seeds of bread. The results of testing the accuracy of the Monte Carlo method in predicting the amount of bread production using MAPE, resulting in a fairly small error value of 9.43%. So this research is quite appropriate to be used as a method of predicting the amount of bread production. Keywords: Prediction, Production, Monte Carlo, LCM